2020
DOI: 10.2967/jnumed.119.239624
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT in the Diagnostic and Treatment Evaluation of Pediatric Posttransplant Lymphoproliferative Disorders

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…But in one study, it was reported that false-negative results were confirmed in the Waldeyer's ring, cervical lymph nodes and small bowel being interpreted as physiological uptake in paediatric PTLD patients. 16 So we must persist with further investigation including tissue biopsy if there is a high clinical suspicion of PTLD. In our study, all the patients were diagnosed by histopathology and treated according to their individual pathological subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But in one study, it was reported that false-negative results were confirmed in the Waldeyer's ring, cervical lymph nodes and small bowel being interpreted as physiological uptake in paediatric PTLD patients. 16 So we must persist with further investigation including tissue biopsy if there is a high clinical suspicion of PTLD. In our study, all the patients were diagnosed by histopathology and treated according to their individual pathological subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…If hypermetabolic lymph nodes or extranodal masses are observed with PET‐CT, then pathological biopsy is needed to confirm the diagnosis. But in one study, it was reported that false‐negative results were confirmed in the Waldeyer's ring, cervical lymph nodes and small bowel being interpreted as physiological uptake in paediatric PTLD patients 16 . So we must persist with further investigation including tissue biopsy if there is a high clinical suspicion of PTLD.…”
Section: Discussionmentioning
confidence: 99%
“…84 6. FDG PET-CT is the recommended imaging modality to screen for PTLD in patients with symptoms and evidence of EBVpositivity (Grade B; SOR 2, moderate recommendation) [85][86][87] (Table 7).…”
Section: 2mentioning
confidence: 99%
“…A recent study involving 28 children with PTLD showed that 18 F-FDG PET/CT has a good positive predictive value (PPV) and specificity, but its sensitivity and negative predictive value (NPV) were poor. This may be because children grow and develop rapidly, and there are high metabolic regions such as the brain, kidneys, and heart that render 18 F-FDG PET/CT unable to detect PTLD that can be confirmed by histology in these regions (12). Studies have shown that the median peak standardized uptake value (SUVpeak) at the biopsy site of monomorphic PTLD is significantly higher than those of the polymorphic and non-destructive subtypes of PTLD.…”
Section: Introductionmentioning
confidence: 99%